Antibody dependent cell cytotoxicity is maintained by the unmutated common ancestor of 6F5, a Gp41 conformational epitope targeting antibody that utilizes heavy chain VH1-2. Issue 31 (29th July 2022) - Wrotniak, Brian H.; Garrett, Meghan; Baron, Sarah; Sojar, Hakimuddin; Shon, Alyssa; Asiago-Reddy, Elizabeth; Yager, Jessica; Kalams, Spyros; Croix, Michael; Hicar, Mark D.
Highlights: Antibodies that target the Gp41 conformational epitope characterized by 6F5 antibody binding are enriched in long-term non-progressors. The unmutated common ancestor of the 6F5 VH1-2 heavy chain retains significant antibody dependent cell cytotoxicity. Targeting vaccine efforts toward antibodies that are functional with germline heavy chain sequences may offer a direct path to immune protection. Abstract: In studies on monoclonal IgG antibodies (mAbs) from long-term non-progressors (LTNPs), our laboratory has previously described highly mutated Abs against a complex conformational epitope with contributions from both gp41 the N terminal and C terminal heptad repeat helices. Despite using the VH1-2 gene segment, known to contribute to some of the broadest neutralizing Abs against HIV, members of these Abs, termed group 76C Abs, did not exhibit broad neutralization. Because of the high number of mutations and use of VH1-2, our goal was to characterize the non-neutralizing functions of Abs of group 76C, to assess if targeting of the epitope correlates with LTNP, and to assess the maturation of these Abs by comparison to their predicted common ancestor. Serum competition assays showed group 76C Abs were enriched in LTNPs, in comparison to VRC-01. Specific group 76C clones 6F5 and 6F11, expressed as recombinant Abs, both have robust ADCC activity, despite their sequence disparity. Sequence analysis predicted the common ancestor of this clonal group would utilize the germline non-mutated variable gene. We produced a recombinant ancestor Ab (76Canc) with a heavy chain utilizing the germline variable gene sequence paired to the 6F5 light chain. Competition with group 76C recombinant Ab 6F5 confirms 76Canc binds HIV envelope constructs near the original group C epitope. 76Canc demonstrates comparable ADCC to 6F5 and 6F11 when using gp41 constructs of both clade B and clade C. The functional capability of Abs utilizing germline VH1-2 has implications for disease control and vaccine development.